Oncological principles in the management of ocular surface squamous neoplasia - A Review - Rolika Bansal; Santosh G Honavar (Indian Journal of Ophthalmology)
Ocular surface squamous neoplasia (OSSN) is the most common neoplasia of the anterior segment. Accurate and timely diagnosis, including detailed clinical assessment and imaging, is essential to ascertain the extent of the disease. The gold standard treatment for OSSN has evolved over the years, transitioning from wide-margin surgical excision using the “no-touch” technique to topical immunotherapy, plaque brachytherapy, and targeted immunotherapy. The choice of treatment modality depends on a tailored approach based on the initial presentation and progression of the disease. This review consolidates a comprehensive understanding of the variable clinical presentations of OSSN, diagnostic and imaging techniques, and available treatment options. It also provides a foundation for the oncologic principles of managing OSSN while offering insights into future therapeutic approaches.